Macrophage Heterogeneity and Plasticity: Impact of Macrophage Biomarkers on Atherosclerosis - Rojas, Joselyn (Scientifica (Cairo), 2015)
Cardiovascular disease (CVD) is a global epidemic, currently representing the worldwide leading cause of morbidity and mortality. Atherosclerosis is the fundamental pathophysiologic component of CVD, where the immune system plays an essential role. Monocytes and macrophages are key mediators in this aspect: due to their heterogeneity and plasticity, these cells may act as either pro- or anti-inflammatory mediators. Indeed, monocytes may develop heterogeneous functional phenotypes depending on the predominating pro- or anti-inflammatory microenvironment within the lesion, resulting in classic, intermediate, and non-classic monocytes, each with strikingly differing features. Similarly, macrophages may also adopt heterogeneous profiles being mainly M1 and M2, the former showing a proinflammatory profile while the latter demonstrates anti-inflammatory traits; they are further subdivided in several subtypes with more specialized functions. Furthermore, macrophages may display plasticity by dynamically shifting between phenotypes in response to specific signals. Each of these distinct cell profiles is associated with diverse biomarkers which may be exploited for therapeutic intervention, including IL-10, IL-13, PPAR-γ, LXR, NLRP3 inflammasomes, and microRNAs. Direct modulation of the molecular pathways concerning these potential macrophage-related targets represents a promising field for new therapeutic alternatives in atherosclerosis and CVD.